Effects of Vegetable Transplanter Press Wheel Design on Soil Compaction and Seedling Establishment - Mohanty, D. K.; Behera, D.; Mahapatra, M.; Swain, S. K. (Journal of Agricultural Engineering, 2017)
Studies were conducted on an experimental two-row self-propelled semi-automatic vegetable transplanter through control plot conditions to determine the optimum press wheel parameters for achieving maximum plant stand of brinjal crop. Brinjal seedling length of 150-300 mm was transplanted at forward speed of 0.8-1.0 km.h-1. Plant stand increased and soil cone index decreased with increase in tilt angle from 5° to 15°, and also with increase in width of the press wheel from 55 mm to 75 mm for different tilt angles, and press wheel diameters of 55, 65 and 75 mm. It was also found that larger the diameter of press wheel, better was the plant stand in a row. Best performance of the press wheel was obtained at dimensions of 15º tilt angle, 300 mm diameter and 75 mm width.